Comparative Study of the Influence of Full and Partial Halo Geomagnetic Storms on High Latitude Ionosphere - Obiegbuna, Dominic Chukwuebuka; Okeke, Francisca Nneka; Okpala, Kingsley Chukwudi; Orji, Orji Prince; Egba, Gregory Ibeabuchi; Ugonabo, Josephine Obiageli (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2021)
We have studied and compared the effects of full and partial halo geomagnetic storms on the high latitude ionosphere. The study used the total electron content (TEC) data obtained from the global positioning system (GPS) to examine the level of response of high latitude ionosphere around Ny Alesund, Norway to full and partial halo geomagnetic storms of June 23rd 2015 and January 1st 2016 respectively. This study was carried out using a dual frequency ground based GNSS observations at high latitude (NYAL: 78.56oN, 11.52oE) ionospheric station in Norway. The vertical TEC (VTEC) was extracted from Receiver Independent Exchange (RINEX) formatted GPS-TEC data using the GOPI Software developed by Seemala Gopi. The GOPI software is a GNSS-TEC analysis program which uses ephemeris data and differential code biases (DCBs) in estimating slant TEC (STEC) prior to its conversion to VTEC. From the results, the responses of the high latitude before the storm days were more positive than on the storm days. Also the overall response of the high latitude to the full halo geomagnetic storm was more positive with more impact than that of the partial halo geomagnetic storm.